Translational control of UIS4 protein of the host-parasite interface is mediated by the RNA binding protein Puf2 in Plasmodium berghei sporozoites - Silva, Patrícia A. G. C. (2022)
Copyright: © 2016 Silva et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.